Strength and permeability properties of sodium silicate-sodium dihydrogen phosphate grouted sand - Mollamahmutoğlu, Murat; Avcı, Eyubhan; Deveci, Emre; Gokce, Aydın; Yıldırım, Eray (Springer Science and Business Media Deutschland GmbH, 2021)
In this study, it was aimed at investigating the injection performance of sodium silicate-sodium dihydrogen phosphate grouts into different graded sand samples, the time-dependent strength, and the permeability properties of injected specimens under different curing conditions. At first, the viscosity, gel time, and syneresis of grout mixtures were determined based on the contents of grout components included in grout mixtures. Syneresis is the process that causes the grout gel to shrink due to the exudation of liquid. While the unconfined compressive strength (UCS) of air-dried samples increased with time (varied from 740 kPa and 1529 kPa at the end of the 150th day), the UCS of wet-cured specimens decreased with time (ranged from 49 kPa and 293 kPa at the end of 150th day). The air-dried strengths of M4, M6, and M9 grouted specimens were 11.8, 8.39, and 5.77 times greater than those of wet-cured specimens, respectively. The permeability of various graded sand specimens was decreased with sodium silicate-sodium dihydrogen phosphate grouts under both wet-cured and air-dried conditions. As the decrease in the permeability of wet-cured specimens was one to four orders of magnitude, the decrease in the permeability of wet-cured specimens was two to five orders of magnitude
Keywords: Permeability; Sand; Sodium dihydrogen phosphate; Sodium silicate; Strength